Indonesia: Managing Decentralization - Ahmad, Ehtisham; Mansoor, Ali M. (International Monetary Fund, 2002)
The process of decentralization in Indonesia was initiated after a long period of autocratic rule. Despite the political imperatives, there is a need to carefully sequence the fiscal decentralization to ensure that financing follows the assignment of functions. The functions should be commensurate with the capacity to provide public services. The paper argues for the proper sequencing to avoid jeopardizing macroeconomic stability or the effective delivery of public services.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

Agricultural supply response and poverty in Mozambique - Heltberg, R.; Tarp, F. (Food Policy, 2002)
This paper identifies key causal factors behind farmers’ marketing decisions in Mozambique. A two-step decision making process is outlined. Farmers decide, first, whether or not to participate in the market. Next, they decide how much to sell. The model is estimated using a Heckman switching regression approach. The key importance of non-price factors such as risk, technology and transport infrastructure come out clearly. Marginal effects are calculated for poor and nonpoor households and broken down into a market participation and a quantity (sales value) component. The marginal effects for the poor are not substantially different from those of the nonpoor. This suggests that differences in area-based characteristics (especially risk and technology) are more influential in the commercialization process than differences in how the poor and the nonpoor respond to incentives. Moreover, interventions to promote market access are likely to solicit a greater volume of additional supply from peasants entering the market for the first time than from existing market participants stepping up their production and sales. To achieve pro-poor rural growth it is essential to address explicitly the conditions of high-risk, low productivity and low capital endowments of poor farmers.
Keywords: G - Mozambique / Moçambique; L - english / inglês

Discovering normality in health and the reproductive body : proceedings of a workshop held at the Program of African Studies Norhtwestern University - Bledsoe, Caroline; LaRay, Denzer; Glassman, Jonathon; Schoenbrun, David; Ebeling, Mary F. E.; Hansen, Karen Tranberg (Pas, 2002)
The papers and discussions included in this collection are the product of a workshop, “Discovering Normality in Health and the Reproductive Body,” held in March, 2001 at Northwestern University's Program of African Studies. The idea for the workshop stemmed from a history of collaborations among Caroline Bledsoe, Jane Guyer, and Kuate Defo Barthélemy on topics of fertility, health, and research methodology. The workshop itself grew out of a commitment to continue that conversation and to expand it to a wider range of people and disciplines. The disciplines represented were wideranging indeed. They included sociocultural anthropology, biological anthropology, history, reproductive biology, history of medicine, public health, and obstetric medicine. The focus of the workshop was Africa, but we also included important comparative cases on South Asia and the Netherlands. In addition we have included those of the discussants' excellent and provocative comments that were available, some of the rapporteurs' notes, and a full list of the participants.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; ⛔ No DOI found

Improving Health for the Poor in Mozambique: The Fight Continues - Chao, Shiyan; Kostermans, Kees (International Bank for Reconstruction and Development / The World Bank, 2002)
The health sector in Mozambique has made significant progress in terms of increasing coverage of services. However, health remains a major concern in the area of poverty reduction. The study describes the health status of the population, especially of the poor, and how the sector responds to the needs. Huge inequalities continue to exist with regards to resource allocation, deployment of staff and availability of services among various geographic areas, between the urban and rural population, and between the poor and the non-poor. The study builds upon the existing studies on health and consolidates the sector knowledge. Based on the analysis, the study makes various recommendations on how the health sector reforms can be made more pro-poor by focusing on certain interventions, by targeting certain areas and population groups, by designing new delivery models that would bring the services closer to the population, and by improving financial management to serve the poor more effectively.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; access to services / acesso a serviços; health / saúde; poverty / pobreza